2012
DOI: 10.1071/zo12008
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA analyses of the saltwater crocodile (Crocodylus porosus) from the Northern Territory of Australia

Abstract: The saltwater crocodile is distributed throughout south-east Asia and Australia. In Australia, it is most abundant in the Northern Territory and Queensland, where it is sustainably farmed for its skins and meat. The aim of this study was to elucidate the relationships and genetic structure among saltwater crocodiles from the Northern Territory of Australia using mitochondrial control region sequences from 61 individuals, representing nine river basins and six of unknown origin, as well as published sequences f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 36 publications
1
1
0
Order By: Relevance
“…The study reveals that the variability in the 1,806 bp of mtDNA analysed here is low. The low level of variation in the mtDNA sequences is concordant with reports of low levels of mtDNA variation reported in other crocodilian species (Bloor et al, 2015;Glen et al, 2002;Luck et al, 2012;Posso-Pelaez et al, 2018;Ray et al, 2004). However, the homogeneity of the hypervariable control region is unusual.…”
Section: Discussionsupporting
confidence: 87%
“…The study reveals that the variability in the 1,806 bp of mtDNA analysed here is low. The low level of variation in the mtDNA sequences is concordant with reports of low levels of mtDNA variation reported in other crocodilian species (Bloor et al, 2015;Glen et al, 2002;Luck et al, 2012;Posso-Pelaez et al, 2018;Ray et al, 2004). However, the homogeneity of the hypervariable control region is unusual.…”
Section: Discussionsupporting
confidence: 87%
“…The proportion of sequences from each of the CERV clades did not appear to vary from the overall average proportion of sequences recovered across all locations (Table 1). Although recent genetic studies have revealed some level of diversity among animals from the same or similar sampling locations [29,30], a comparison with the current dataset was not possible as different regions of the genome (mtDNA and gene coding regions) were used in these studies.…”
Section: Resultsmentioning
confidence: 99%